Assessing Measurement Quality of Multidimensional Classroom Incivility Scale in Higher Education - Asfiati, Asfiati; Cahyadi, Ani; Hendryadi, Hendryadi; Hartinah, Sitti (Frontiers in Education, 2022)
Incivility probably occurs in most classrooms across cultures. The aim of this study was to: (1) confirm the reliability and validity of a measure of classroom incivility within an Indonesian context, and (2) determine whether subscales (or factors) of incivility would emerge on this scale. Data were collected from 517 participants through two stages of online questionnaire distribution. A principal component analysis (PCA) to test the initial structure and seven stages of PLS-confirmatory composite analysis (PLS-CCA) were used to evaluate the measurement quality. Classroom incivility is best represented as a multidimensional structure with class disruption (7items), disrespect communication (7 items), inappropriate student behaviors (5 items), and integrity violation (3 items) constituting the best factor solution. In line with this hypothesis, classroom incivility is negatively related to civility and prosocial behavior, and no significant difference was found between groups of males and females. Higher education institutions in Indonesia can use this instrument as a supplementary tool to evaluate the level of classroom incivility. We also discussed the practical implications in educational settings in general and suggestions for future research on classroom incivility in non-Western countries. The results of this study are helpful to administrators in building a climate of civility and more dynamic learning environment.